2005
DOI: 10.1021/bi0475323
|View full text |Cite
|
Sign up to set email alerts
|

The Micelle-Bound Structure of an Antimicrobial Peptide Derived from the α-Chain of Bovine Hemoglobin Isolated from the TickBoophilus microplus

Abstract: Hemoglobin is known to be a source of peptides involved in several functions. The peptide FLSFPTTKTYFPHFDLSHGSAQVKGHGAK (Hb33-61) is a proteolytic product of the bovine hemoglobin alpha-chain found in the gut content of the cattle tick, Boophilus microplus, and it possesses antimicrobial activity. Since in the past we showed that the amidated form of Hb33-61, Hb33-61a, is active against a few Gram-positive bacteria and fungi strains at micromolar concentration [Fogaca et al. (1999) J. Biol. Chem. 274, 25330-25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 58 publications
2
31
0
14
Order By: Relevance
“…The amino acid sequence revealed this peptide was a fragment of the bovine α-hemoglobin and a synthetic peptide identical to the native peptide showed antimicrobial activity against Gram-positive bacteria and fungi at micromolar concentrations (Fogaça et al, 1999). Sforca et al (2005) upon further investigation showed that this α-hemoglobin fragment functions by disrupting the bacterial membrane. Nakajima et al (2003b) also reported the purification of two rabbit α-hemoglobin fragments from the midgut lumen of Ornithodoros moubata.…”
Section: Cystatinsmentioning
confidence: 99%
“…The amino acid sequence revealed this peptide was a fragment of the bovine α-hemoglobin and a synthetic peptide identical to the native peptide showed antimicrobial activity against Gram-positive bacteria and fungi at micromolar concentrations (Fogaça et al, 1999). Sforca et al (2005) upon further investigation showed that this α-hemoglobin fragment functions by disrupting the bacterial membrane. Nakajima et al (2003b) also reported the purification of two rabbit α-hemoglobin fragments from the midgut lumen of Ornithodoros moubata.…”
Section: Cystatinsmentioning
confidence: 99%
“…Este peptídeo, denominado Hb 33-61, apresenta massa molecular de 3.205 Da e atividade contra bactérias gram-positivas e fungos, e corresponde aos aminoácidos 33 a 61 da subunidade α da hemoglobina bovina (Fogaca et al, 1999). A estrutura terciária do peptídeo sinté-tico de carboxila amidada, Hb 33-61a, foi elucidada por espectroscopia de ressonância magnética nuclear (RMN) na presença de micelas de dodecil sulfato de sódio (SDS), sugerindo que a molécula é responsável pela permeabilização da membrana plasmática de agentes patogênicos, tais como a levedura Candida albicans (Sforca et al, 2005). Posteriormente outras hemocidinas foram identificadas nesta mesma espécie de carrapato (Cruz et al, 2010).…”
Section: Hemoglobina Como Fonte De Peptídeos Bioativosunclassified
“…O estudo de análogos do Hb33-61 nas formas amidada e com carboxila livre revelou que a amidação provoca aumento significativo da atividade frente a Candida albicans. Por apresentar propriedades biológicas e estruturais idênticas às do Hb33-61a, o Hb40-61a pareceu ser a sua porção mínima ativa [Sforça et al (2005) Biochemistry 44, 6440-51; Machado et al (2007) Biopolymers 88, 413-26]. Para comprovar tal sugestão, no presente trabalho, sintetizamos, purificamos e caracterizamos novos análogos do Hb33-61a, bem como os avaliamos quanto às suas atividades frente a C. albicans e Micrococcus luteus.…”
Section: à Minha Família E Amigos Com Imenso Carinhounclassified
“…Apesar da baixa similaridade nas suas seqüências de aminoácidos, a maioria dos peptídeos antimicrobianos é catiônica (TABER, 2002 KIM et al, 2000) e o fragmento 33-61 da cadeia α da hemoglobina bovina (FOGAÇA et al, 1999, SFORÇA et al, 2005, MACHADO et al, 2007.…”
Section: Peptídeos Antibióticosunclassified
See 1 more Smart Citation